2021
DOI: 10.1007/s11136-021-02761-0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and impact on quality of life in adulthood: development and validation of a short difficult childhood questionnaire in a large population-based health survey

Abstract: Purpose A short adverse childhood experiences (ACEs) measure is needed with non-intrusive items that include subjective evaluations of childhood. We validated a short Difficult Childhood Questionnaire (DCQ) that assesses ACEs using personal perceptions of events. Methods The study relied on 2019 data from a representative survey (N = 28,047) in Norway. We examined the DCQ’s factor structure, internal consistency, and discriminant validity in a multi-group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
1
17
0
1
Order By: Relevance
“…In a previous study, items 1, 3, and 4 were validated together in a short, Difficult Childhood questionnaire (DCQ). The discriminant and convergent validities of the tool were confirmed (16) in the same population that we analyzed in the current study.…”
Section: Adverse Childhood Experiencessupporting
confidence: 73%
See 1 more Smart Citation
“…In a previous study, items 1, 3, and 4 were validated together in a short, Difficult Childhood questionnaire (DCQ). The discriminant and convergent validities of the tool were confirmed (16) in the same population that we analyzed in the current study.…”
Section: Adverse Childhood Experiencessupporting
confidence: 73%
“…Many previous ACE-related studies focused on mapping the types and frequencies of ACEs. In contrast, the present study invited participants to report selfperceptions of the consequences and severity of ACEs, which may be more relevant in assessing experiences that cause detrimental effects on adult perceptions of quality of life (6,16).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In a previous study, we suggested that ACEs, such as parental divorce and alcohol problems, and lacking a trustworthy adult, are associated with enduring perceptions of personal childhood hardships. Accordingly, we introduced and validated a short Difficult Childhood Questionnaire (DCQ) that captures the subjective burden of childhood adversities (Vederhus et al, 2021). With such a tool, research may better be able to examine potential mediators, such as negative affect and social isolation, through which ACEs exert their influence on adult health (Shevlin et al, 2015).…”
Section: Mediators Between Aces and Adult Quality Of Lifementioning
confidence: 99%
“…Perceived childhood difficulties. The survey used the Difficult Childhood Questionnaire (DCQ), which had three items that assessed retrospectively quarrelling and conflicts in the family environment; memories about adverse experiences during childhood due to loss, violence or abuse; and a general evaluation of childhood (Vederhus et al, 2021). The questions were scored on a 5-point ordinal scale.…”
Section: Potential Mediators Between Aces and Adult Qolmentioning
confidence: 99%
“…Those who reported their childhood as difficult or very difficult were categorized with “poor quality of childhood”. The overall quality of the single item question of childhood has earlier been used in large Norwegian public health study (the HUNT study) ( 114 ), and Vederhus, Timko ( 115 ) indicated that the question would could be an empirically supported method of assessing adverse childhood events (ACEs).…”
Section: Methodsmentioning
confidence: 99%